Smallholder irrigation schemes in the Limpopo Province, South Africa - van Koppen, Barbara; Nhamo, Luxon; Xueliang Cai; Gabriel, M. J.; Sekgala, M .; Shikwambana, S.; Tshikolomo, K.; Nevhutanda, S.; Matlala, B.; Manyama, D. (International Water Management Institute, 2017)
A survey of 76 public smallholder irrigation schemes in the Limpopo Province was jointly conducted by the International Water Management Institute (IWMI), Department of Agriculture, Forestry and Fisheries (DAFF), South Africa, and the Limpopo Department of Agriculture and Rural Development (LDARD), as part of the ‘Revitalization of Smallholder Irrigation in South Africa’ project. About one-third of those schemes was fully utilized; one-third partially utilized; and one-third not utilized in the winter of 2015; however, no single socioeconomic, physical, agronomic and marketing variable could explain these differences in utilization. Sale, mostly for informal markets, appeared the most important goal. Dilapidated infrastructure was the most important constraint cited by the farmers. The study recommends ways to overcome the build-neglect-rebuild syndrome, and to learn lessons from informal irrigation, which covers an area three to four times as large as public irrigation schemes in the province.